2003
DOI: 10.1080/713713593
|View full text |Cite
|
Sign up to set email alerts
|

Osteogenic Differentiation is Selectively Promoted by Morphogenetic Signals from Chondrocytes and Synergized by a Nutrient Rich Growth Environment

Abstract: Cartilage formation always precedes that of bone during endochondral skeletal development. To determine if chondrocytes provide inductive signals for osteogenesis, C3H10T(1/2) mesenchymal stem cells were co-cultured in membrane separated transwell culture chambers with chondrocytes, osteoblasts, or fibroblasts. Osteogenesis, as assessed by the expression of osteocalcin mRNAs, was strongly induced in the C3H10T(1/2) cells co-cultured with chondrocytes but not induced by co-culture with either osteoblasts or fib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(36 citation statements)
references
References 0 publications
2
34
0
Order By: Relevance
“…Some studies have utilized mixed populations of cells plated together in monolayer [39], whereas others have employed cell culture insert culture systems [40] or conditioned medium [41] to study the interaction of cells without direct contact. Biomaterials can provide the added dimension of a 3D environment for cell and tissue coculture.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have utilized mixed populations of cells plated together in monolayer [39], whereas others have employed cell culture insert culture systems [40] or conditioned medium [41] to study the interaction of cells without direct contact. Biomaterials can provide the added dimension of a 3D environment for cell and tissue coculture.…”
Section: Discussionmentioning
confidence: 99%
“…For example, during endochondral ossification, cartilage serves as a morphological template for blood vessel invasion and MSC recruitment for future bone [88]. Recent studies have indicated that morphogenetic signals from chondrocytes regulate multiple steps of chondrogenesis and endochondral ossification during skeletal differentiation [98][99][100]. These studies have implicated that mechanisms of endochondral ossification of condensing mesenchyme can be regulated by cell-secreted morphogenetic factors.…”
Section: Growth Factors-mentioning
confidence: 99%
“…1 Later studies investigating cell differentiation identified a number of factors that could play a role in the communication between chondrocytes and osteoblasts in during differentiation. Cell communication through paracrine signaling has demonstrated that it plays a role in the selective osteogenic differentiation of MSC when exposed to soluble factors secreted by nonhypertrophic chondrocytes cultured in a transwell membrane system 22,23 (Fig. 2B).…”
Section: Indirect Coculturesmentioning
confidence: 99%
“…The physically distinct locations of the cell populations help track individual phenotype changes and gene expression characteristics. [21][22][23]27,35 The shared media volume also aids in accounting for factors that may be constitutively expressed by one or more of the cell populations, as well as for any temporal changes in the secretory protein expression profile that is typical of many primary cell populations involved in tissue regeneration.…”
Section: Indirect Coculturesmentioning
confidence: 99%
See 1 more Smart Citation